TOPICALITY OF ETHNOPSYCHOLOGICAL PREREQUISITES IN BEHAVIORAL ECONOMICS MODELS, IN A MONO-ETHNIC CULTURAL ENVIRONMENT - Hovsepyan, N.S. (Modern Psychology, 2019)
The purpose of this article is to analyze the known approaches of the economic ethno psychology, which will allow us to identify the features of economic behavior in monoethnic environment such as Armenia. In different countries, the issues of economic ethno psychology have different nuances, which are related to demographic, socio-political, cultural and national factors (scale, size, movement and density of population, average life expectancy, economic well-being, social stratification, mono or poly-national features, traditions, rituals, etc.). Thus, the chosen problem cannot be solved in the scope of the one specific scientific sphere; therefore, we will rely on the theoretical and empirical methods of psychology and at the same time use the scientific concepts of philosophy, sociology, culturology and economics.